Critical factors associated with the haccp system implementation in food colombian companies (@limentech, Ciencia y Tecnología Alimentaria, 2022)
The Food Safety Management system based on Hazard Analysis and Critical Control Points (HACCP) is a key element in the production of safe food for human consumption. This study aims to explore the main critical factors associated with the successful application of HACCP system in Colombian food and beverage industry. A measurement instrument was validated by experts and empirically collected data through a non-probabilistic sample. The results suggest that the commitment and qualification of human talent contribute significantly to the success of the HACCP system implementation. Likewise, an effective system implementation favors the growth of the industry in the market, guarantees customer satisfaction, and promotes process improvement. This study allows companies to understand the key critical factors for decision-making on the planning and implementation processes of the HACCP system, as a source of competitive advantage for the industry in globalized markets
Keywords: food safety; competitiveness; barriers; motivations; profits; management systems